Recent developments in the conduct of Latin American agricultural research: Paper prepared for the International Conference on Agricultural Science and Technology, Beijing, November 7-9, 2001 - Beintema, Nienke M.; Pardey, Philip G. (International Service for National Agricultural Research, 2001)
Following two decades of increasing investments, growth in public agricultural research spending in Latin America stalled during the 1980s, reflecting shrinking government contributions and declining donor support in the midst of general economic crises. Data for more recent years show some signs of recovery with an average rate of growth for an 11-country sample of 4 percent per year during the first half of the 1990s (compared with 1 percent during the 1980s). Nonetheless, this regional trend masks significant variation among the various countries. The regional averages are also heavenly influenced by developments in Mexico and Brazil; two countries that accounted for almost two-thirds of total Latin American agricultural research investment in the mid-1990s. Over the past few decades the organization of agricultural research in Latin America has changed considerably, becoming institutionally more complex and fragmented in many countries. In addition, some shifts in the sources of funding have occurred as well as changes in the way funds are dispersed."-- Authors' Abstract